The Integration of Pancasila Values and the Values of Rahmatan lil-Alamin: A Perspective on the Merdeka Curriculum in Madrasah Ibtidaiyah - Saridin, Saridin (The Future of Education Journal, 2024)
Madrasah Ibtidaiyah (MI) is an Islamic-based basic education institution which aims to produce a superior generation intellectually, spiritually and morally. With approaches such as the Independent Curriculum and the integration of the Project for Strengthening Student Profiles of Pancasila and Rahmatan lil alamin (P5P2RA). The objectives of this research are: analyzing the harmony between the values ​​contained in the Pancasila Student Profile and the concept of Rahmatan lil alamin values ​​through P5P2RA. The method in this research is qualitative with a literature study approach. The results of this research are: the integration of Pancasila and rahmatan lil alamin values ​​through P5P2RA at Madrasah Ibtidaiyah is a strategic effort to shape the character of students who are religious, nationalist and contribute positively to society. With an interactive and contextual project-based learning (PBL) approach, students not only understand values ​​such as mutual cooperation, tolerance and social justice theoretically but also practice them in real life. Teachers play a central role as facilitators, guiding students in designing and implementing projects while acting as role models in implementing these values. Despite facing challenges such as limited resources and teacher understanding, the implementation of P5P2RA can be successful with the support of the Independent Curriculum policy, collaboration with the community, and utilization of local potential, making it a program that strengthens students' character while preparing them to make real contributions to society and the environment.